Pulling ourselves up by our bootstraps: The greenhouse gas value of products, enterprises and industries - Ulf von Kalckreuth (Deutsche Bundesbank, 2022)
This paper presents a system of greenhouse gas indicators for markets and policymakers. The system is lean and informative. It condenses the relevant product and enterprise-specific information into a single number: the greenhouse gas (GHG) value. Like prices, GHG values are easy to understand, manage and communicate. The envisaged scenario is one in which, at all levels of production, goods and services have two tags - the financial price to pay and the GHG value. GHG values are interdependent. The value for any product will depend on the carbon costs of all inputs. This paper shows that the massive information processing this simultaneity involves can be handed over to the market. Analytically, the system of product-level indicators is solved for the reduced form, the vector of true GHG values. This vector is shown to be the fixed point to which measurement will converge if producers comput e GHG values using the information they have: data from their input providers if available, and estimates elsewhere. This amounts to a process of collective, decentralised learning. Technological changes will automatically be accounted for. A micro-simulation exercise is carried out based on sectoral information on production structure from Germany. The results indicate that convergence is fast. W ith appropriate institutional underpinning, the disclosure of GHG values by producers may become self-sustaining.
Keywords: Q56; Q51; C81; 330; greenhouse gas intensities; carbon accounting; green finance